Biomanagement of metal-contaminated soils - Khan, Mohammad Saghir (Environmental pollution, 2011)
Heavy-metal contamination is one of the world's major environmental problems, posing significant risks to agro-ecosystems. However, conventional technologies for metal-contaminated soil remediation have often been expensive and disruptive.   This book provides comprehensive, state-of-the-art coverage of the natural, sustainable alternatives that use a wide range of biological materials in the removal/detoxification of heavy metals, consequently leading to the improvement of crops in these soils.  Novel, environmentally friendly and inexpensive solutions are presented based on a sound understanding of metal contamination and the roles of plants and microbes in the management of these toxic soils.   Written by more than forty worldwide experts drawing on their wealth of experience in this field, the book provides not only the necessary scientific background but also addresses the challenging questions that require special attention in order to better understand metal toxicity in soils and its management through bioremediation.   This book will be of interest to a wide range of students/researchers/practitioners specializing in the areas of environmental microbiology, soil pollution, sustainable development, crop science, soil biology, and related disciplines.  It will be especially useful to anyone engaged in identifying metal-contamination problems and trying to solve them through the application of natural and inexpensive biological materi